Early Birds: Poems for Junior Secondary Schools Book 2 - Osundare, Niyi (Spectrum Books Ltd, 2004)
The peoms in this series are designed to make you think as you sing, to help you discover the beauty of poetry as a companion of music and the product of human imagination$1! =s
Keywords: Non-Fiction; Poetry